Wedding night ebook A novel. - Kinsella, Sophie (2013)
The #1 New York Times bestselling author of The Party Crasher and Love Your Life returns with her trademark blend of sparkling wit and playful romance in this page-turning story of a wedding to remember—and a honeymoon to forget.   “Sophie Kinsella keeps her finger on the cultural pulse, while leaving me giddy with laughter.”—Jojo Moyes, author of The Giver of Stars and The Last Letter from Your Lover Lottie just knows that her boyfriend is going to propose, but then his big question involves a trip abroad—not a trip down the aisle. Completely crushed, Lottie reconnects with an old flame, and they decide to take drastic action. No dates, no moving in together, they’ll just get married . . . right now. Her sister, Fliss, thinks Lottie is making a terrible mistake, and will do anything to stop her. But Lottie is determined to say “I do,” for better, or for worse. Praise for Wedding Night “[A] fun novel that’s as light and bubbly as a glass of wedding champagne.” — USA Today “Filled with laugh-out-loud moments, this is Sophie Kinsella at her wittiest. . . . An engrossing novel.” — Bookreporter “You won’t be able to stop reading. . . . The narrative gallops along with humorous scenes and great one-liners.” — The Daily Mail “A fast-paced, hilarious comedy [with] a charming cast of characters.” —Kirkus Reviews